Pre-Freudian recurrence: Photography and the trace before the uncanny - Zahar, Iwan; Mustaqim, Karna; Maulana, Salman; Damayantie, Irma; Wahyudi, Tri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This practice-led research proposes recurrence as a systematic photographic method, where Derrida's concept of iterability is achieved through controlled visual iteration. Through recurrence, identical objects undergo transformation across iterations because variations in light, motion and environmental conditions produce perceptual instability rather than visual sameness. This process produces uncanny effects identifiable through perceptual ambiguity (Jentsch), environmental transformation and reappearance of overlooked materials (Schelling). The work engages pre-Freudian concepts of the uncanny - Jentsch's intellectual uncertainty and Schelling's definition of the uncanny as ``something that should have remained hidden but has returned to light.'' Waste materials, typically ignored or excluded from conscious attention, return through the photographic process. Forest fire residues, overgrown with vegetation, reappear across iterations. However, uncanny effects are not uniform. Burning leaves activate Jentsch's perceptual ambiguity only. Trash can activate both Schelling and Jentsch: Schelling is always activated (revealing hidden dumping), while Jentsch is activated only when the trash is made of deformable materials (fabric, jute, thin plastic) that change shape when thrown, not from rigid materials (bottles, hard containers) that retain their form. Each image marks a moment of recurrence, where the object's appearance is reconfigured through subject selection, material intervention (burning, iterative throwing), environmental conditions (light, weather, time of day), and photographic techniques (flash, exposure control). Uncanny effects are selectively achieved through iterative trials, in which unsuccessful images fail to produce perceptual instability